Ice slurry ingestion during cycling improves Olympic distance triathlon performance in the heat - Stevens, C. J.; Dascombe, B.; Boyko, A.; Sculley, D.; Callister, R. (Journal of Sports Sciences, 2013)
This study investigated the effect of ice slurry ingestion during a triathlon on intragastric temperature and 10 km running performance in the heat. Nine well-trained male triathletes performed two randomised trials of a simulated Olympic distance triathlon in hot conditions (32-34°C). Exercise intensity during the swim (1500 m) and cycle (1 hr) legs was standardised, and the 10 km run leg was a self-paced time trial. During the cycle leg, either 10 g · kgBM-1 of ice slurry (< 1°C) or room temperature fluid (32-34°C) was ingested. In the run leg of the ice slurry trial, performance time (43.4 ± 3.7 vs. 44.6 ± 4.0 min; P = 0.03), intragastric temperature (at 1.5 km; 35.5 ± 1.2 vs. 37.5 ± 0.4°C; P = 0.002) and perceived thermal stress (at 5 km; 73 ± 9 vs. 80 ± 7 mm; P = 0.04) were significantly lower. Oxygen consumption was significantly higher in the ice trial between 9.5-10 km (52.4 ± 3.4 vs. 47.8 ± 5.4 mL/kg· min; P = 0.04). The results suggest ice slurry ingestion was an effective ergogenic aid for triathlon running performance in the heat. The attenuation of intragastric temperature and perceived thermal stress were likely contributors to the self-selection of a higher running intensity and improved performance time.